PENDAMPINGAN PENGEMBANGAN USAHA UMKM BARU DI KOTA CIREBON DENGAN EKOSISTEM MODEL BISNIS CANVAS - Magdalena, Lena; Hatta, Muhammad; Febima, Mesi (STKIP PGRI SITUBONDO, 2025)
The intense competition in the business world presents various challenges that can threaten economic stability, making it essential for entrepreneurs to develop effective strategies to run their businesses. This community service program is designed using a participatory approach based on adult-learning processes, focusing on the introduction and implementation of the Business Model Canvas (BMC). The activity is organized by Catur Insan Cendekia University (CIC) in collaboration with the Department of Cooperatives, Micro, Small, and Trade Enterprises (DKUMPP) of Cirebon City, involving 100 fostered MSMEs. The implementation method includes several stages: (1) delivering material using PowerPoint presentations and simulations related to the BMC concept, (2) interactive discussions, (3) training on drafting BMC for new MSMEs to address the challenges of the new normal era, and (4) evaluating the program's impact on MSME participants in the region. Entrepreneurs are provided with insights on how to run their businesses using the nine key elements of BMC, which include value proposition, customer segments, channels, customer relationships, key resources, key activities, key partnerships, revenue streams, and cost structures. The expected outcomes of this program are: (1) scientific publications in international community service journals, (2) activity publication in print or online media, (3) signing of a Cooperation Agreement (SPK) with partners, and (4) development of a BMC document to support new MSME ventures.